1995
DOI: 10.1093/jmedent/32.5.583
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Comparison of Feeding Success Among Triatoma infestans, T. guasayana, and T. sordida (Hemiptera: Reduviidae)

Abstract: Success in obtaining a blood meal and rapid access to hiding places after feeding are the principal requirements triatomines have as they colonize artificial ecotopes. Feeding success and postfeeding location of 3rd and 5th instars of Triatoma sordida (Stål), of T. guasayana Wygodzinsky & Abalos, and T. infestans (Klug) were studied in an experimental box in which triatomines and a chicken were left to interact overnight. The bird was enclosed in a glass cube, slightly raised to allow triatomines to get in and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 0 publications
0
10
1
Order By: Relevance
“…We know very little about the distribution of triatomines inside a dwelling. Even if all the stages are found in the upper part of the walls 17,28 , our results suggest that males and females rest in a stratified manner on the walls, males being above of females. Domestic cockroaches have a similar way of life than triatomines, except the feeding habits.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…We know very little about the distribution of triatomines inside a dwelling. Even if all the stages are found in the upper part of the walls 17,28 , our results suggest that males and females rest in a stratified manner on the walls, males being above of females. Domestic cockroaches have a similar way of life than triatomines, except the feeding habits.…”
Section: Discussioncontrasting
confidence: 57%
“…Animals can exhibit locomotion that is gravitationally directed vertically down or up (positive or negative geotaxis, respectively). Geotaxis in triatomine has been poorly described, T. infestans was just reported as being more concentrated in the upper half of the walls in houses or chicken houses 17,28 . Moreover, to our knowledge, no studies were conducted to analyze the synergy or conflict between gregariousness and geotaxis in triatomines.…”
Section: Introductionmentioning
confidence: 99%
“…In studies about the vertical distribution of T. infestans in Brazilian dwellings, adults, nymphs, and eggs of this species tended to be concentrated in the upper half of the wall 24 . In northern Argentina, 58.3% of a domestic T. infestans population obtained after the demolition of a house were in the roof, and eggs were aggregated at the top of the walls, decreasing gradually towards the floor (in 36 ). In experiments using an artificial chicken house, T. infestans assembled at the upper part of the walls (in 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Animals can exhibit locomotion that is gravitationally directed vertically down or up (positive or negative geotaxis, respectively). Geotaxis in triatomine has been poorly described, T. infestans was just reported as being more concentrated in the upper half of the walls in houses or chicken houses 24,36 . Moreover, to our knowledge, no studies were conducted to analyze the synergy or conflict between gregariousness and geotaxis in triatomines.…”
Section: Introductionmentioning
confidence: 99%
“…Crocco & Catalá (1997), comparing insects fed on doves and rodents, found that meal average weight was greater for insects feeding on rodents. However, the relationship between weight changes and the quantity of blood ingested has not yet been established (Wisnivesky‐Colli et al , 1995; Pereira et al , 1998; Guarneri et al , 2000b; Soares et al , 2000). The most immediate question concerns the differences between these two host mammal species that might explain the present results.…”
Section: Discussionmentioning
confidence: 99%